Impact of COVID-19 Pandemic on Consumer Behavior towards Online Shopping in Punjab, Pakistan - Huma, Zill-E-; Hafeez, Muhammad Haroon; Athar, Nida; Raza, Mahum (Pakistan Journal of Humanities and Social Sciences, 2025)
The objective of this research is to examine the influence of pandemic on the purchase behavior of customers. Based on this objective, this research aims to explore utilitarian consumption pattern, hedonic consumption pattern, food supply security, and contact limitations that influenced the consumer intention towards online shopping under the mediating role of consumer preference in Pakistan context. For collecting an authentic and reliable data, an online random survey was conducted. 225 valid responses were collected from customers in Punjab, Pakistan. Structural equation modeling technique was employed to analyze the data. According to its outcomes, a significant influence of utilitarian consumption pattern, hedonic consumption pattern, food supply chain and contact limitation in COVID-19 pandemic on the Pakistani consumers’ intention towards online shopping has developed. Within these relationships, consumer preference is acting as a significant mediator that strengthened their influence, except the hedonic consumption pattern's influence on dependent variable. Overall, this research will give new direction of research to the local, national and international communities to ponder on e-commerce businesses’ importance in the changing consumer environment. But its methodological and contextual gaps can be covered by future researchers in their upcoming researches.